Evidence of sporulation capability of the ubiquitous oil reservoir microbe Halanaerobium congolense. Issue 4 (1st April 2021) - Jones, Aaron A.; Pilloni, Giovanni; Claypool, Joshua T.; Paiva, Antonio R.; Summers, Zarath M.
Abstract: Subsurface lineages of microorganisms are often questioned for their autochthonous nature. We hypothesize that sporulation is critical to the delivery and ubiquity of Halanaerobium congolense in global subsurface hydrocarbon reservoirs, forming spores, or spore-like structures in order to survive surface conditions, and thriving in subsurface reservoir conditions. Genomic analysis of H. congolense revealed the presence of various genes essential for sporulation, many of which are homologous to those involved in various stages of sporulation in clostridia and bacilli. Transcriptomics revealed transcription of sporulation genes in H. congolense grown in sub-optimal conditions. This is further supported by microscopy evidence of spore-like structures.